STRENGTH AND MICROSTRUCTURE OF COLD-ROLLED IF STEEL - Anh-Hoa Bui; Hoang Le (Acta Metallurgica Slovaca, 2016)
With the emerge of vacuum technology, it is possible to produce ultra low carbon (ULC) steels with carbon content of less than 0.005 %mass which is called interstitial free (IF) steels. In this study, strength and microstructure of IF steel after cold-rolling have been determined. The initial steel plates were cold-rolled using two different cold reductions (CR) as 80 and 90% in total, thereafter the steel sheets were cut into specimens for tensile test and optical microscopy. Ultimate tensile strength (UTS) of the cold-rolled steel was high (650807 MPa), but the elongation (EL) was low (3.55.3%). Meanwhile, UTS of the annealed steels was decreased to 290 MPa when soaking temperature was 800oC because of stress relief and recrystallization. It was concluded that higher CR (more severe deformation) increased the strength but decreased the ductility of the IF steels. In consistence with micrograph of the steels, X-ray diffraction (XRD) results showed that microstructure of the cold-rolled and annealed IF steels was only ferrite. Textures, one of the most important factors affecting the recrystallization, were found in cold-rolled steels.